2015
DOI: 10.1080/22201181.2015.1089666
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the choice of anaesthesia as a field of specialty in University of Ghana School of Medicine and Dentistry, Korle-Bu Teaching Hospital

Abstract: Background: Specialisation is perceived as essential for success, and affects the availability and distribution of medical personnel and the quality of service the health system is able to deliver. In Ghana, some areas of medical specialties have a relatively good number of practitioners and are constantly attracting prospective doctors into these fields. Anaesthesia, which is an essential and integral part of the health care system, is one field with an inadequate workforce and has been attracting few doctors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…3,5,6,[11][12][13]16 In addition, studies performed solely among medical students showed that anaesthesiology was infrequently indicated as a career choice, which was attributed to insignificant exposure during undergraduate training. 14,15,17,21,22 Increasing undergraduate exposure to anaesthesiology should be considered to improve the visibility of the discipline among medical students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,5,6,[11][12][13]16 In addition, studies performed solely among medical students showed that anaesthesiology was infrequently indicated as a career choice, which was attributed to insignificant exposure during undergraduate training. 14,15,17,21,22 Increasing undergraduate exposure to anaesthesiology should be considered to improve the visibility of the discipline among medical students.…”
Section: Discussionmentioning
confidence: 99%
“…4,[6][7][8] Differences between gender have been identified, with females increasingly opting for specialties allowing for part-time work. 3,9 Studies on choosing anaesthesiology as a career have been conducted in developing countries, [10][11][12][13] including African countries such as Rwanda 14 and Ghana, 15 that have a severe shortage of anaesthetists. The findings of these studies are similar to those in developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have looked at factors that influence the career preferences of medical graduates. 1,2 Such factors include the individual's characteristics, personal interest, perceived benefits of the discipline, prestige, attractiveness of particular specialties, and exposure to a specialty in the undergraduate medical curriculum. 3,4 The main reasons in our cohort (the undergraduate rotation in medical school, time for family and the intellectually stimulating/challenging nature of the discipline) are in keeping with other studies in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have looked at factors that influence the career preferences of medical graduates. [1][2][3] Such factors include the individual's characteristics, perceived benefits of the discipline, attractiveness of particular specialties, and exposure to a specialty in the undergraduate medical curriculum. An understanding of such factors in the local context could have important implications for future recruitment into anaesthesiology.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to emphasize that medical students' career preferences vary among countries and within countries 13 . As maintained by Abdul-Rahman and colleagues 14 , Ghana has an appreciable number of specialists in some areas of the medical practice, with many doctors preferring those specialties over the other ones. This situation tends to affect the medical workforce in some important areas of the healthcare delivery system in Ghana.…”
Section: Introductionmentioning
confidence: 96%